Virtual simulation as an interactive learning environment and its role in supporting interactive learning strategies (The International Journal of Educational Sciences and Arts, 2024)
The problem in this study is manifested in an attempt to investigate the impact of using the virtual learning environment and its multimedia on supporting interactive learning strategies, especially since in some educational cases, direct sensory experiences cannot be used due to their risks, scarcity, cost, or spatial or temporal distance, and in this case, the need for a virtual learning environment becomes a more effective alternative. The objectives of the study were identified as: reviewing the virtual simulation models available for teaching students in the Kingdom of Saudi Arabia, and maximizing the benefit of virtual simulation to support interactive learning strategies to overcome educational stereotypes, and actively engage the student and interact with scientific materials, allowing him to make his own decisions, and not just be a passive recipient of information. The study used the descriptive analytical approach. The most important results of the study were: The necessity of using virtual simulation systems helps support the educational process and increase the efficiency of students, thus improving the educational system as a whole. Virtual simulation can also be used as an interactive educational environment to develop creative thinking by embodying concepts and experimenting with alternative problem-solving strategies. Virtual simulation also provides students with a degree of freedom to enable them to achieve the largest number of creative solutions quickly and appropriately to their abilities. Virtual simulation allows students to control the educational situation to varying degrees. The most important recommendations of the study were: The necessity of using virtual simulation as a function of the educational environment to train students to think creatively, and the necessity of making the most of the capabilities of modern technology to develop teaching methods that suit students in the modern era.
Keywords: Virtual Simulation; Interactive Learning Environment; Interactive Learning Strategies